Gala Dalam Perspektif Konflik Agraria : Kajian Hukum Adat atas Ketidakpastian Hak Pemanfaatan Tanah di Lhokseumawe - Fitria Mardhatillah; Laila Rasyid; Shira Thani (Prodi Ilmu Hukum, Universitas Teuku Umar, 2026)
This article examines gala as a customary legal practice in Aceh, where landowners temporarily transfer their land to another party as collateral in exchange for a sum of money. While intended as a form of mutual trust and economic security, this practice generates legal uncertainty regarding land utilization rights, particularly in the context of agrarian conflicts in Lhokseumawe. Using a combined normative and empirical approach, this study analyzes gala from both the perspective of customary law principles and the lived realities of local communities. Field observations and interviews reveal that although gala continues to be recognized in community practice, its implementation often lacks formal legal certainty, leading to overlapping claims between traditional agreements and state agrarian regulations. Findings highlight that disputes arising from gala are commonly resolved through customary mechanisms rather than litigation, yet this reinforces a dualism between state law and adat law. The study concludes that recognition and harmonization of gala within Indonesia’s agrarian legal framework are essential to prevent protracted disputes, strengthen community land rights, and safeguard social cohesion in Aceh.